2019
DOI: 10.3390/ijerph16203787
|View full text |Cite
|
Sign up to set email alerts
|

Monthly-Term Associations Between Air Pollutants and Respiratory Morbidity in South Brazil 2013–2016: A Multi-City, Time-Series Analysis

Abstract: Most air pollution research conducted in Brazil has focused on assessing the daily-term effects of pollutants, but little is known about the health effects of air pollutants at an intermediate time term. The objective of this study was to determine the monthly-term association between air pollution and respiratory morbidity in five cities in South Brazil. An ecological time-series study was performed using the municipality as the unit of observation in five cities in South Brazil (Gravataí, Triunfo, Esteio, Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…A high concentration of PM directly reduces the visibility of air. It is also well known that PM severely damages public health [22][23][24]. For the Chinese population, Lu et al [25] found that short exposures to PM 2.5 and PM 10 were positively associated with increases in mortality due to cardiovascular and respiratory disease.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A high concentration of PM directly reduces the visibility of air. It is also well known that PM severely damages public health [22][23][24]. For the Chinese population, Lu et al [25] found that short exposures to PM 2.5 and PM 10 were positively associated with increases in mortality due to cardiovascular and respiratory disease.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies on the health effects of air pollutants focused on children [ 25 , 26 ]. Some studies show that increased concentration of PM 10 is associated with the increase of respiratory hospitalization in all age groups, with the most significant impact on the population between 16 and 59 years old [ 27 ]. However, all air pollutants except CO had the most significant impact on the elderly group in our study, the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Children are particularly vulnerable to air pollution because their lung immune system is still developing. A number of studies conducted in different countries have demonstrated an association between long-term or short-term exposure to air pollutants and childhood ALRI hospitalization [10][11][12][13]. There are also several studies from China that have focused on the effects of air pollutants on the hospitalization of children with ALRI.…”
Section: Introductionmentioning
confidence: 99%